Effects of lanthanum complex on the thermo-oxidative aging of natural rubber. (October 2015) - Zheng, Wei; Liu, Li; Zhao, Xiuying; He, Jingwei; Wang, Ao; Chan, Tung W.; Wu, Sizhu
Abstract: Novel mixed antioxidants composed of antioxidant IPPD and lanthanum (La) complex were added as a filler to form natural rubber (NR) composites. Mechanical testing was carried out before and after the thermo-oxidative aging of NR composites. Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR) was performed to observe the variation of internal groups. The thermal and thermo-oxidative decomposition of NR were investigated by thermogravimetric (TG) curves, and the thermo-oxidative aging kinetic parameters were determined by the Flynn-Wall-Ozawa (FWO) method. The results showed that the thermo-oxidative degradation of NR composites was a two-stage reaction. Compared with the pure antioxidant IPPD, the same mass of mixed antioxidants had better effects to improve the mechanical properties of NR composites, reduce the formation of aging products, and increase the activation energies ( E a ) of the thermo-oxidative degradation. Based on the autocatalytic, free radical chain reaction of the thermo-oxidative aging of NR, different function mechanisms of antioxidant IPPD and La complex were also compared. As a result of strong coordination abilities, large coordination numbers, and decomposition of the hydroperoxides, this new rare-earth antioxidant could indeed enhance the thermo-oxidative aging resistance of NR composites. This research has important significance for the exploitation of rubbers with high resistance to thermo-oxidative aging.